Renal sarcoidosis: epidemiological and follow-up data in a cohort of 27 patients - Löffler, Christian; Löffler, Uta; Tuleweit, Anika; Waldherr, Rüdiger; Uppenkamp, Michael; Bergner, Raoul (Sarcoidosis, vasculitis and diffuse lung diseases, 2015)
BACKGROUND: Renal sarcoidosis (RS) is a possible manifestation of systemic sarcoidosis. The clinical presentation can range from asymptomatic individuals up to acute renal failure with the necessity of renal replacement therapy. The definite diagnosis must be established by renal biopsy. - OBJECTIVES: Demonstration of clinical characteristics and effectiveness of steroid treatment. - METHODS: We present a single center study of 27 patients with histologically proven RS. Firstly, we elaborate on descriptive features such as extra-renal organ involvement, calcium levels, renal function, proteinuria and histological subtypes and provide an histological assessment of renal damage. Secondly, we present follow-up data over a period of 2 years or more. - RESULTS: Non-granulomatous tubulointerstitial nephritis (ngIN) was the most common histological entity (44%), followed by granulomatous IN (GIN, 30%), IgA-GN (26%) and nephrocalcinosis (11%). Under treatment with oral prednisone mean eGFR significantly improved from 38 ± 21 ml/min to 57 ± 26 ml/min and proteinuria decreased from 981 ± 304 mg/24 hrs to 176 ± 77 mg/24 hrs at the end of follow-up. In total, 62.5% of patients responded to therapy. - CONCLUSIONS: We demonstrated that GIN is more often associated with advanced stages of renal insufficiency than any other histological manifestation of RS. Furthermore, prednisone therapy is effective in improving eGFR and in reducing total urinary protein secretion. We suggest that the key prognostic factor for renal survival in RS is the early response to treatment.